FEATURES OF PURINE METABOLISM AND MICROALBUMINURIA OF ISCHEMIC HEART DISEASE IN PATIENTS WITH METABOLIC SYNDROME - Tashtemirova I. M; Qosimov I.S (Scholar Express Journals, 2024)
To study the state of purine metabolism and microalbuminuria in patients with metabolic syndrome
Keywords: Metabolism And Microalbuminuria; Metabolic syndrome